USING AND METHODS OF FORMATION OF KINSHIP ADDRESES IN CHINESE LANGUAGES - Koybakova, А (Journal of Oriental Studies, 2016)
Kinship addresses in the Chinese people very perfect mate system. In comparison with other language and the amount of handling large finely distributed. Each family member are given a separate treatment. The formation of these outstanding cultural characteristics influenced people of this nation. This article discusses the using and methods of formation of kinship addreses in chinese and leading examples.